The frequency of NSAIDs Use in orthopedic patients in tertiary hospital (The Planet, 2022)
Objective: In this study our main goal is to identify the frequency of NSAIDs use in orthopedic patients. Method: This cross-sectional study was carried out at tertiary care hospital, in the department of orthopedics. Where data were collected from January 2019 to January 2020. During the study, a total of 100 patients of orthopedic   department   who   have   used   or   will   be   using NSAIDs for more than a week were include. Sample were collected through purposive sampling as per inclusion criteria. Results: During the study, most of the patients were belong to 47-57 years. 30.8% and majority were male. Arthritis was   the   most   common indication   for   NSAIDs   (42%) followed     by     Knee arthritis 29% and Spinal diseases 13%. Majority cases 45% prescribed to Aceclofenac followed by Lornoxicam cases were 25%, 15% were Diclofenac, 10% were Etoricoxib. During discharge 60% patients prescribed with Proton pump inhibitors (PPIs). Conclusion: NSAIDs were the frequently prescribed drugs in the orthopedic OPD where Aceclofenac mostly prescribed. Most of the cases to avoid GI tract conditions PPI were prescribed during discharge.
Keywords: non-steroidal anti-inflammatory drugs (NSAIDs); orthopedics; Proton pump inhibitors (PPIs)